Influence of chemical properties on soil carbon storage of a tropical peat swamp forest - Satrio, Anton Eko; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: It is important to investigate the seriousness of degradation of peat swamp forest caused by skidding system in terms of its function as a carbon sink. In this study, we formulated assumptions that conditions of our research site before the introduction of skidding system were in their natural states, thus that changes measured are clearly caused by skidding system. The objective of this study was to determine soil carbon storage of a tropical peat swamp forest in their natural state. Approach: Peat soil samples and bulk density were taken at 0-15 cm in a 0.3 ha plot at Sibu, Sarawak, Malaysia. The soil samples were analyzed for acidity, organic matter content, total carbon and total nitrogen. The humic acid extraction was also done and soil carbon storage values obtained by calculation. The calculation of carbon storage was by the bulk density method. Correlation analysis was used where applicable using Statistical Analysis System (SAS) version 9.1. Results: The results indicated that this tropical peat swamp forest rich in soil organic matter (97.645 %) but had extreme acidic environment (pH 3.737), thereby inhibiting organic matter decomposition rates. This tropical peat swamp forest also had large amounts of total carbon (48.823 %), low mineral nitrogen (0.896 %) and high C/N ratio (58.427). Stable carbon (soil carbon storage) positively correlated with unstable carbon (p<0.01, r = 0.43). The value of soil carbon storage was found to be 67.550 Mg Ha-1 (±61.49 % of unstable carbon). Furthermore, soil carbon storage positively correlated with soil organic matter (p<0.01, r = 0.43), total carbon (p<0.01, r = 0.43) and humic acid yield (p<0.01, r = 1.00). However, soil carbon storage negatively correlated with soil acidity (p<0.01, r = -0.55). Conclusion: From the results, it can be concluded that the tropical peat swamp forest indicates its specific natural state. This natural tropical peat swamp forest plays an important role as a sink rather than a source of carbon. The soil carbon storage in this natural tropical peat swamp forest was derived from unstable carbon and sensitive to soil acidity.